Preparation method of degradable hemostatic sponge
By using polylactide/polycaprolactone/polyethylene glycol copolymer polyurethane material, combined with the steps of solution configuration, prefreezing and freeze-drying, a hemostatic sponge with good hemostatic effect and uniform degradation characteristics was prepared, solving the problem of poor hemostatic effect of existing materials in nasal and ear canal surgery.
Patent Information
- Application Number
- CN202510308662.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-04-25
AI Technical Summary
The existing postoperative tamponous materials have low appearance flatness, unstable sponge contraction rate, easy to concave center, low strength, slow rebound and uneven degradation in nasal and ear canal surgery, which affects the hemostatic effect.
Polylactide/polycaprolactone/polyethylene glycol copolymer polyurethane material is used to prepare a hemostatic sponge with a flat appearance, uniform pore size, good resilience and uniform degradation through the steps of solution configuration, prefreezing and freeze-drying.
The sponge has a flat appearance, uniform pore size, good resilience and uniform degradation speed, which improves the hemostatic effect and reduces the risk of rejection and infection.
Smart Images

Figure CN119868624A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of medical devices, and in particular to a method for preparing a degradable hemostatic sponge. Background Art
[0002] Nasal and ear canal surgeries are widely performed worldwide. These surgical areas are characterized by small space, dense blood vessels and easy bleeding. Traditional suture hemostasis methods are not applicable in these areas. Therefore, the use of packing materials for hemostasis after surgery has become an effective treatment option. Packing materials can not only stop bleeding during surgery, but also prevent postoperative bleeding, tissue adhesion and restenosis of the cavity. While ensuring the hemostatic effect, alleviating the patient's discomfort is a key consideration when selecting postoperative packing materials, which has always been the focus of attention in the medical community.
[0003] Over the past decade, ear and nasal surgery techniques and related instruments have made significant progress, but the development of postoperative packing materials has lagged behind. The development of existing postoperative packing materials can be divided into four stages: (1) The first generation of non-swelling, non-biodegradable materials: represented by vaseline gauze strips, this material is easy to prepare, easy to operate, and suitable for different degrees of bleeding. It has the dual advantages of high cost-effectiveness and stable efficacy. However, due to the lack of coagulant active ingredients, inelasticity and hygroscopicity, it has limitations in effectively controlling bleeding. In addition, its biocompatibility is poor, and it may cause strong irritation after packing. It is easy to combine with blood scab when removed, which may cause discomfort to patients. (2) The second generation of swellable, non-biodegradable materials: represented by polyvinyl alcohol (PVA) sponge, this material has the advantages of fast operation and convenience, soft texture, excellent swelling performance, and excellent blood absorption ability, but it needs to be removed after surgery, there is a risk of secondary bleeding caused by adhesion, and frequent wetting may affect its hemostatic efficacy. (3) ) The third generation of natural biodegradable materials: hemostatic materials represented by alginate, collagen, and hyaluronic acid. The materials are degradable and do not need to be removed after surgery, but they lack the necessary toughness and elasticity; they may increase scars and adhesions and are difficult to clean after surgery; the materials lack elasticity and have poor blood absorption performance; (4) The fourth generation of synthetic biodegradable polymer materials: degradable polyurethane synthetic biodegradable polymer materials represented by nano-absorbent cotton. This type of material has excellent elasticity and flexibility, can effectively compress and stop bleeding, degrades quickly, does not require secondary surgery to remove, does not cause new trauma, can promote epithelial tissue growth, reduce scar formation, avoid nasal adhesions, and keep the surgical cavity clean. Among them, the advent of the fourth generation of biodegradable hemostatic sponges has significantly improved the postoperative comfort of patients undergoing nasal and ear canal surgery. However, this type of sponge has problems such as low appearance flatness, unstable sponge shrinkage rate, easy depression in the center, low strength resulting in slow rebound, and uneven degradation. These problems will affect the hemostatic effect.
[0004] Therefore, in order to address the problems of low appearance flatness, unstable sponge shrinkage, easy center depression, low strength leading to slow rebound, and uneven degradation that affect the hemostatic effect, a method for preparing a degradable hemostatic sponge can be designed. Summary of the invention
[0005] In order to overcome the problems of low appearance flatness, unstable sponge shrinkage rate, easy depression in the center, low strength leading to slow rebound and uneven degradation, which affect the hemostatic effect.
[0006] The technical solution of the present invention is: a method for preparing a degradable hemostatic sponge, the steps of which are as follows: Step 1: dissolving polylactide / polycaprolactone / polyethylene glycol copolymer polyurethane material in a solvent to prepare a polyurethane solution; Step 2: Place the polyurethane solution at a temperature of -5°C to 5°C for 5 to 24 hours, stir it evenly, pour it into a mold, cool it to -40°C, and perform pre-freezing treatment; Step 3: Freeze-dry the pre-frozen sample to obtain a hemostatic sponge with a smooth appearance, uniform pore size, good resilience, and uniform degradation rate.
[0007] Preferably, the intrinsic viscosity of the polylactide / polycaprolactone / polyethylene glycol copolymer polyurethane material is 0.5 to 2.0 dL / g.
[0008] Preferably, the mass ratio of the three components in the polylactide / polycaprolactone / polyethylene glycol copolymer polyurethane material is 2:6:2 to 4:1:5.
[0009] Preferably, the solvent is 1,4-dioxane.
[0010] Preferably, the mass volume concentration of the polyurethane solution is 1 g / 10 mL to 1 g / 40 mL.
[0011] Preferably, the mold temperature is 0°C to 5°C.
[0012] Preferably, the cooling rate is 1 to 10°C / hour.
[0013] Preferably, the freeze-drying temperature is -40°C to 10°C, and the freeze-drying time is 24 to 72 hours.
[0014] Preferably, the hemostatic sponge is used for packing and hemostasis after nasal cavity and ear canal surgery.
[0015] The beneficial effects of the present invention are as follows: through the three steps of solution preparation, pre-freezing and freeze-drying, the hemostatic sponge has the characteristics of smooth appearance, uniform pore size, good resilience and uniform degradation rate. The structure of the sponge can absorb a large amount of blood and quickly and effectively control bleeding, so the hemostatic effect is better. In addition, experimental results show that the hemostatic sponge prepared by the present invention can be degraded at a uniform rate and gradually decomposed and absorbed in the body, reducing the risk of rejection reaction and infection. The preparation method is simple, which solves the problem that the degradable hemostatic sponge prepared by the traditional freeze-drying method has an uneven surface and a concave center. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Shown is the hemostatic sponge prepared in Example 1 of the present invention; Figure 2 Shown is the hemostatic sponge prepared in Comparative Example 1 of the present invention; Figure 3 Shown is the hemostatic sponge prepared in Example 3 of the present invention; Figure 4 Shown is the hemostatic sponge prepared in Comparative Example 2 of the present invention; Figure 5 Shown is the SEM image of the hemostatic sponge of Example 2 of the present invention; Figure 6 Shown is the SEM image of the hemostatic sponge of Comparative Example 1 of the present invention; Figure 7 Shown is the SEM image of the hemostatic sponge of Example 3 of the present invention; Figure 8 Shown is the SEM image of the hemostatic sponge of Comparative Example 2 of the present invention; Fig. 9 Shown is a comparison chart of sponge degradation of Example 3 of the present invention and Comparative Example 2. DETAILED DESCRIPTION
[0017] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0018] Example 1 (1) Solution preparation: Dissolve polylactide / polycaprolactone / polyethylene glycol copolymer polyurethane material with an intrinsic viscosity of 0.5 dL / g and a composition mass ratio of 2:6:2 in 1,4-dioxane to prepare a solution with a mass volume concentration of 1 g / 10 mL; (2) Prefreezing: Place the above solution at -5°C for 5 hours, stir it evenly, pour it into a mold at 0°C, and cool it to -40°C at a rate of 10°C / hour; (3) Freeze drying: Freeze-dry the pre-frozen sample at -40℃-10℃ for 24 to 72 hours to obtain a hemostatic sponge with a smooth appearance, uniform pore size, good resilience, and uniform degradation rate.
[0019] Example 2 (1) Solution preparation: Dissolve polylactide / polycaprolactone / polyethylene glycol copolymer polyurethane material with an intrinsic viscosity of 2.0 dL / g and a composition mass ratio of 4:1:5 in 1,4-dioxane to prepare a solution with a mass volume concentration of 1 g / 40 mL; (2) Prefreezing: Place the above solution at 5°C for 24 hours, stir it evenly, pour it into a mold at 5°C, and cool it to -40°C at a rate of 10°C / hour; (3) Freeze drying: Freeze-dry the pre-frozen sample at 10°C for 72 hours to obtain a hemostatic sponge with a smooth appearance, uniform pore size, good resilience, and uniform degradation rate.
[0020] Comparative Example 1 (1) Solution preparation: Dissolve polylactide / polycaprolactone / polyethylene glycol copolymer polyurethane material with an intrinsic viscosity of 2.0 dL / g and a composition mass ratio of 4:1:5 in 1,4-dioxane to prepare a solution with a mass volume concentration of 1 g / 40 mL; (2) Prefreezing: Pour the above solution into a mold and prefreeze at -40°C for 6 hours; (3) Freeze-drying: Freeze-dry the pre-frozen sample at 10°C for 72 hours to obtain a sponge.
[0021] Example 3 (1) Solution preparation: Dissolve polylactide / polycaprolactone / polyethylene glycol copolymer polyurethane material with an intrinsic viscosity of 1.2 dL / g and a composition mass ratio of 3:1:2 in 1,4-dioxane to prepare a solution with a mass volume concentration of 1 g / 25 mL; (2) Prefreezing: Place the above solution at 0°C for 12 hours, stir it evenly, pour it into a mold at 2°C, and cool it to -40°C at a rate of 5°C / hour; (3) Freeze drying: Freeze-dry the pre-frozen sample at -20°C for 48 hours to obtain a hemostatic sponge with a smooth appearance, uniform pore size, good resilience, and uniform degradation rate.
[0022] Comparative Example 2 (1) Solution preparation: Dissolve polylactide / polycaprolactone / polyethylene glycol copolymer polyurethane material with an intrinsic viscosity of 1.2 dL / g and a composition mass ratio of 3:1:2 in 1,4-dioxane to prepare a solution with a mass volume concentration of 1 g / 25 mL; (2) Prefreezing: Place the above solution at room temperature for 12 hours, stir it evenly, pour it into a mold, and prefreeze it at 0°C for 8 hours; (3) Freeze-drying: Freeze-dry the pre-frozen sample at -20°C for 48 hours to obtain a hemostatic sponge.
[0023] Example 4 (1) Solution preparation: Dissolve polylactide / polycaprolactone / polyethylene glycol copolymer polyurethane material with an intrinsic viscosity of 1.5 dL / g and a composition mass ratio of 4:1:4 in 1,4-dioxane to prepare a solution with a mass volume concentration of 1 g / 35 mL; (2) Prefreezing: Place the above solution at 4°C for 15 hours, stir it evenly, pour it into a mold at 0°C, and cool it to -40°C at a rate of 3°C / hour; (3) Freeze drying: Freeze-dry the pre-frozen sample at 0°C for 36 hours to obtain a hemostatic sponge with a smooth appearance, uniform pore size, good resilience, and uniform degradation rate.
[0024] Example 5 (1) Solution preparation: Dissolve polylactide / polycaprolactone / polyethylene glycol copolymer polyurethane material with an intrinsic viscosity of 0.8 dL / g and a composition mass ratio of 3:3:3 in 1,4-dioxane to prepare a solution with a mass volume concentration of 1 g / 20 mL; (2) Prefreezing: Place the above solution at 0°C and let it stand for 10 hours. After stirring evenly, pour it into a mold at 0°C and cool it to -40°C at a rate of 3°C / hour. (3) Freeze drying: Freeze-dry the pre-frozen sample at -30°C for 54 hours to obtain a hemostatic sponge with a smooth appearance, uniform pore size, good resilience, and uniform degradation rate.
[0025] Example 6 (1) Solution preparation: Dissolve polylactide / polycaprolactone / polyethylene glycol copolymer polyurethane material with an intrinsic viscosity of 1.0 dL / g and a composition mass ratio of 2:6:4 in 1,4-dioxane to prepare a solution with a mass volume concentration of 1 g / 30 mL; (2) Prefreezing: Place the above solution at 5°C for 24 hours, stir it evenly, pour it into a mold at 0°C, and cool it to -40°C at a rate of 5°C / hour; (3) Freeze drying: Freeze-dry the pre-frozen sample at 0°C for 48 hours to obtain a hemostatic sponge with a smooth appearance, uniform pore size, good resilience, and uniform degradation rate.
[0026] Example 7 (1) Solution preparation: Dissolve polylactide / polycaprolactone / polyethylene glycol copolymer polyurethane material with an intrinsic viscosity of 1.8 dL / g and a composition mass ratio of 4:1:4 in 1,4-dioxane to prepare a solution with a mass volume concentration of 1 g / 40 mL; (2) Prefreezing: Place the above solution at -5°C for 6 hours, stir it evenly, pour it into a mold at 0°C, and cool it to -40°C at a rate of 1°C / hour; (3) Freeze drying: Freeze-dry the pre-frozen sample at -30°C for 72 hours to obtain a hemostatic sponge with a smooth appearance, uniform pore size, good resilience, and uniform degradation rate.
[0027] Example 8 (1) Solution preparation: Dissolve polylactide / polycaprolactone / polyethylene glycol copolymer polyurethane material with an intrinsic viscosity of 1.3 dL / g and a composition mass ratio of 4:4:3 in 1,4-dioxane to prepare a solution with a mass volume concentration of 1 g / 30 mL; (2) Prefreezing: Place the above solution at -1°C for 8 hours, stir it evenly, pour it into a mold at 0°C, and cool it to -40°C at a rate of 8°C / hour; (3) Freeze drying: Freeze-dry the pre-frozen sample at 10°C for 24 hours to obtain a hemostatic sponge with a smooth appearance, uniform pore size, good resilience, and uniform degradation rate.
[0028] Experimental Example 1: Appearance Observation Direct observation and taking pictures with a camera show that Example 2 ( Figure 1 ) and Example 3 ( Figure 3 ) has a smooth appearance, while Comparative Example 1 ( Figure 2 ) and Comparative Example 2 ( Figure 4 ) There are obvious dents on the appearance.
[0029] Experimental Example 2: Aperture Observation The surface morphology of the sponge was observed by scanning electron microscope. Figure 5 ) and Example 3 ( Figure 7 ) has uniform pore size, and the comparative example 1 ( Figure 6 ) and Comparative Example 2 ( Figure 8 ) has messy pores and uneven pore sizes.
[0030] Experimental Example 3: Hemostatic sponge resilience test The samples of Examples 1-8 of the present invention and Comparative Examples 1-2, which have a length and width of 2 cm respectively, were compressed to 20% of the sample height, and the pressure was removed. The time it took for the sponge to recover to its original height was recorded. The results are shown in the following table: It can be seen that the time for Examples 1-8 to recover to their original height is very fast, all within 0.3 seconds, indicating that their elasticity is very good, while the time for Comparative Examples 1 and 2 to recover is more than 2 seconds, and their elasticity recovery is slow.
[0031] Experimental Example 4: Degradation Experiment The hemostatic sponge prepared in Example 3 and the sample of Comparative Example 2 were added to 10 mL of PBS buffer, sealed, and placed in a 37°C water bath shaker. The sponges were taken out for observation at different time points and photographed and recorded ( Fig. 9 ), and its degradation weight loss rate is shown in the following table: As can be seen from the table above, the weight loss of Example 3 is uniform, while that of Comparative Example 2 is slow at first and then fast. Fig. 9 It can be seen that the sponge of Example 3 on the upper side degrades gradually and evenly, while the sponge of Comparative Example 2 on the lower side degrades slowly at first and then accelerates.
[0032] Experimental Example 5: Hemostasis Experiment 10 New Zealand white rabbits were taken, and bleeding wounds were caused in the nasal cavity with a blade. The hemostatic sponges of Examples 1-8 were cut to a suitable size, and the sponges were clamped with tweezers and stuffed into the wounds. In addition, the samples of Comparative Examples 1 and 2 were taken separately and stuffed into the bleeding site as control examples. The hemostatic time was observed. The shorter the time, the better the hemostatic effect. The results are shown in the following table: It can be seen from the above table that the hemostatic time of Examples 1-8 is all within 20 seconds, and the hemostatic time of Comparative Examples 1-2 is all greater than 60 seconds. Therefore, the hemostatic effect of the Examples is better than that of the Comparative Examples.
[0033] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of those skilled in the art without departing from the spirit of the present invention.
Claims
1. A method for preparing a degradable hemostatic sponge, characterized in that: The steps are as follows: Step 1: dissolving polylactide / polycaprolactone / polyethylene glycol copolymer polyurethane material in a solvent to prepare a polyurethane solution; Step 2: After the polyurethane solution is allowed to stand for a period of time, it is poured into a mold for pre-freezing; Step 3: Freeze-dry the pre-frozen sample to obtain a hemostatic sponge with a smooth appearance, uniform pore size, good resilience, and uniform degradation rate.
2. The method for preparing the degradable hemostatic sponge according to claim 1, characterized in that: The intrinsic viscosity of the polylactide / polycaprolactone / polyethylene glycol copolymer polyurethane material is 0.5 to 2.0 dL / g.
3. The method for preparing the degradable hemostatic sponge according to claim 1, characterized in that: The mass ratio of the three components in the polylactide / polycaprolactone / polyethylene glycol copolymer polyurethane material is 2:6:2 to 4:1:
5.
4. The method for preparing the degradable hemostatic sponge according to claim 1, characterized in that: The solvent is 1,4-dioxane.
5. The method for preparing the degradable hemostatic sponge according to claim 1, characterized in that: The mass volume concentration of the polyurethane solution is 1g / 10mL to 1g / 40mL.
6. The method for preparing the degradable hemostatic sponge according to claim 1, characterized in that: In step 2, the standing treatment is: standing the polyurethane solution at -5°C to 5°C for 5 to 24 hours and stirring evenly.
7. The method for preparing the degradable hemostatic sponge according to claim 1, characterized in that: The mold temperature of the mold is 0°C to 5°C.
8. The method for preparing the degradable hemostatic sponge according to claim 1, characterized in that: The cooling rate of the pre-freezing treatment is 1-10°C / hour, and the terminal temperature is -40°C.
9. The method for preparing the degradable hemostatic sponge according to claim 1, characterized in that: In step three, the freeze-drying temperature is -40°C to 10°C, and the drying time is 24 to 72 hours.
10. The preparation method according to claim 1, characterized in that: The hemostatic sponge is used for packing and stopping bleeding after nasal cavity and ear canal surgery.